Professional Identity and Struggles of Basic Level English Teacher: A Critical Narrative Inquiry - Karki, Debraj (Journal of Research and Development, 2021)
Professional development is a continuous process of learning to empower professional competency and enable teachers to be strong and competent in their professional career. The study critically explores the struggles and professional activities of basic level English teachers in professional development. Critical narrative inquiry has been used in relation to long lived experiences of a participant with a semi – structured telephonic interview. The participant narrates three distinct phases of experiences in teaching profession. The result revealed that participant was innately interested in teaching profession before involvement. But the situated school system discouraged his ideology of teaching profession even he determined to continue his profession involving in different seminars, workshop and study. However, the study further suggests that there is lack of innovating teaching profession from critical perspectives focusing the interactive and transformative environment in classroom. Therefore, the basic level teachers need to re- examine and re – construct the professional activities to address the need, interest and level of learners. Similarly, the study contributes to apply language teaching activities in terms of transformative mood rather than structured model of teaching empowering teachers as an agency.